Revista do Norte: a impressão fotográfica e a impressão social da São Luís no começo do século XX - SILVA, Amanda da Silva e (2019)
This paper presentes an investigation about Revista do Norte (North Journal), a literature and art publication, ilustrated with photographs, produced and printed in Maranhão, by Antônio Lobo and Alfredo Teixeira, lasting 5 years, from 1901 to 1906. The scope of this research is to know what purposes the work is like the representations of the city that guide the publication of the images in the magazine, as well as the documents for the editors in the assembly of the photographic material. The reserarch contextualizes Revista do Norte and its directors in the history of illustrated press, not only in Maranhão, but in the entire country by the late 19th and early XIX century, featuring some illustrated journals published in Maranhao, as well as the typographic development and the progress on the technical processes of reproduction and printing images. It is noteworthy the Teixeira Tipogravura and the graphic work done for the jornal.Understand, thus, what we were the discourses of practices and representations (CHARTIER, 1982), which is a magazine to move to the photographs chosen to illustrate a publication. For this, it was necessary to identify and analyze the social place in which the magazine was inserted and the scenario that the city of São Luís was imminent in the early 20th century. The magazine was generated from a project of Alfredo Teixeira together with the journalist Antônio Lobo, one of the leaders of the group of Maranhão intellectuals, called the New Athenians (1890-1930). The research group on the circumstance of the economic and cultural decadence of the city of São Luís in the late 19th and early 20th century. This group wanted to present a reaction aiming to change this situation and resume the speech of a glorious past of material and cultural wealth and mostly literary from that generation that created the epiphet of Atenas Brasileira (Brazilian Athens). To understand the creation of the mythological Brazilian Athens, we resort to the critical explanation on the speeches created and held through centuries, based mainly on the studies of Borralho (2011) and Martins (2006). Lastly, based on an interdisciplinary dialogue, we will confront the images as representations of the city related by historiography, the press and literature.